Rancang Bangun Sistem Penyiram dan Pemupuk Otomatis Menggunakan Fuzzy Logic Berbasis Internet of Things (IoT) - Nadia Miranda; Ahmad Taqwa; Abdul Rakhman (Program Studi Teknik Informatika Universitas Pamulang, 2025)
This research aims to design and build an automatic watering and fertilization system for moon orchids (Phalaenopsis) based on the Internet of Things (IoT) using the Fuzzy Logic method. Moon orchids have slow growth and are affected by environmental factors such as temperature and humidity, where the optimal temperature ranges from 25-27°C and air humidity between 60-85%. The system is designed to monitor and control the plant's environmental conditions in real time, as well as perform automatic watering when the soil humidity is below 35% and stop it when it is above 35%. Tests showed error rates between the various sensors used, such as a difference of 1.61% between the DHT22 temperature sensor and a thermometer, 1.78% for humidity between the DHT22 sensor and a hygrometer, and 8.32% between the soil moisture sensor and a soil moisture meter. The Purple Bloom application used in this system experienced an average delay of 6.11 seconds caused by the speed of the internet. Although there is a slight delay, this system provides convenience and efficiency in the maintenance of moon orchids. The use of IoT technology and artificial intelligence shows great potential in improving the productivity and efficiency of plant care.